(untitled) (Global Journal of Human-Social Science, 2021)
Vision is the most crucial sense among the five senses Almost 80 percent of all learning is achieved through the visual channel Good vision is therefore paramount for learners to reach their academic potential Lack of it can negatively affect how a learner performs in examinations Available studies have looked at the performance of learners with visual impairment in specific subjects The aim of the study was therefore to explore the general performance of learners with visual impairment in summative evaluation in special schools in Kenya A survey design with qualitative research method was adopted Examination results from four special schools for learners with visual impairment were analyzed and in addition a questionnaire was used to solicit more information from teachers who taught the classes under study Descriptive statistics were used to analyze data and findings were presented in tables and percentages Findings indicated that learners with visual impairment generally performed poorly in examinations Mathematics and sciences were the worst done at secondary school level where as Kiswahili and Social studies were the two worst performed at primary school level